AB0886 A Quality of Life (QOL) Study of 100 Children with Juvenile Idiopathic Arthritis (JIA) from Northern India. (15th July 2016) - Agarwal, M.; Sawhney, S.; Mittal, S.
Abstract : Background: JIA affects many domains of a child's life. The patient with JIA has a lot to cope with: Physical pain, medicine intake (both parenteral and oral), clinic appointments, phlebotomy, exclusion from school and social activities during disease flares and anxiety about disease.JIA has an impact on the child's physical, mental and psychosocial health. There is a lacuna in the assessment of Pediatric QoL in these children from our country, we thus undertook this study. Objectives: 1) To assess the QoL score of JIA patients using i) Pediatric rheumatology quality of life (PRQL) score [1] and ii) Pediatric quality of life 3.0 rheumatology module(PedsQL) score [2]. 2) To assess the clinical and socioeconomic factors that may impact the QoL. 3) To correlate PRQL and PedsQL Methods: 100 consecutive children with JIA, 2–18 yr, attending Ped rheumatology unit during a 8 week period were evaluated for QoL. PRQL (parent & child version) PedsQL (parent & child version) & CHAQ (Childhood Health Assessment Questionaire) [3] were completed. Entry criteria was JIA patients with at least 6 months of disease. Results: 46 girls & 54 boys with a median age of 11 yrs (2–18 yrs). Median age:6.2 yrs at disease onset, 7.62yrs at diagnosis. 28 children had clinically active disease on the day of QoL assessment. Age:2–4 yr:8, 5–7 yr.:18, 8–12 yr.:35 and 13–18 yr.:39.Diagnosis: SOJIA: 31, ERA: 42, PJIA:14, OJIA:13.Socio economic indicators: Mother's literacy status: Unlettered 4, primary schooling 10, High school 12, Senior school 7, Graduates 37, Post graduates 30.Stay at home mothers:85, working 15. 19 children belonged to lower socioeconomic strata. Children with clinically active disease had poorer QoL as compared to clinically inactive group (Mann-Whitney test: p<0.00).QoL indicators and CHAQ had no statistical correlation. PRQL and PedsQL were in agreement with each other (Spearman's rho, r=0.72) and both parent and child versions were in concordance. Conclusions: Both PRQL and PedsQL are appropriate tools to assess QOL in JIA. Clinical disease activity status impacts QoL adversely.There was no difference in QoL of children from various socioeconomic strata, nor did the parental education or professional status impact it. References: Weiss PF et al. The pediatric rheumatology QoL scale: validation of the English version in a US cohort of JIA. PROJ.2013;11:43 Varni JWet al.The PedsQL in pediatric rheumatology: reliability, validity, and responsiveness of the pediatric QoL inventory generic core scales and rheumatology module. Arthritis Rheum. 2002;46 (3):714–725 Dempster H et al. The clinical meaning of functional outcome scores in children with juvenile arthritis.Arthritis Rheum. 2001;44(8):1768–74 Disclosure of Interest: None declared